Acute Kidney Injury in Diabetes Mellitus - D. Patschan; G. A. Müller (International Journal of Nephrology)
Diabetes mellitus (DM) significantly increases the overall morbidity and mortality, particularly by elevating the cardiovascular risk. The kidneys are severely affected as well, partly as a result of intrarenal athero- and arteriosclerosis but also due to noninflammatory glomerular damage (diabetic nephropathy). DM is the most frequent cause of end-stage renal disease in our society. Acute kidney injury (AKI) remains a clinical and prognostic problem of fundamental importance since incidences have been increased in recent years while mortality has not substantially been improved. As a matter of fact, not many studies particularly addressed the topic “AKI in diabetes mellitus.” Aim of this article is to summarize AKI epidemiology and outcomes in DM and current recommendations on blood glucose control in the intensive care unit with regard to the risk for acquiring AKI, and finally several aspects related to postischemic microvasculopathy in AKI of diabetic patients shall be discussed. We intend to deal with this relevant topic, last but not least with regard to increasing incidences and prevalences of both disorders, AKI and DM.